Peran Notaris Dalam Rapat Umum Pemegang Saham (RUPS) Terkait dengan Jual Beli Saham (Studi Kasus pada PT. Karya Husada Investama) - , SRIHARYATI; , Prof. Dr. Nindyo Pramono, S.H., M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to examine an under-aged child position as a share holder, to know how share transaction procedures that occurred due to a legacy was, and to know a Notary role in a Share Holder Public Meeting (RUPS) related to that share transaction. This was a normative empirical research that used a secondary and primary data. Data was gathered normative empirically by examining secondary data and in the initial by a document study device that then was continued by a research towards a field primary data by an interview manual device. The research location was conducted in Yogyakarta City, Yogyakarta Special Region Province. The research sample/subject was a respondent i.e. a Notary who was handling RUPS validation on share transaction taking place in PT. Karya Husada Investama in Yogyakarta, while data was analyzed descriptive qualitatively i.e. data obtained from research was presented descriptively and was analyzed qualitatively. Based on the research result and discussion the writer conducted, it could be concluded that: firstly, an under aged child as a share holder had rights as what regulated in Article 52 verse 1 Regulations Number 40 of 2007 on a Limited Company, however due to there was no authority to behave based on Article 47 Regulations Number 1 of 1974 on Marital in performing rights as a share holder, that child was represented by his/her parents. Secondly, share transaction procedures occurred due to legacy prior to be validated by RUPS and informed to The Minister, the beneficiary party as the seller should complete documents namely beneficiary statement letter and death certificate, while for buyer party due to he/she was still under aged, he/she should attach a birth certificate. Thirdly, Notary roles in RUPS not only limited in Act making of Basic Budget amendment and notification to The Minister, however the Notary was obliged to deliver a legal guidance to Act made as what regulated in Article 1 verse 2 point e of Regulations Number 2 of 2014 on Amendment on Regulations Number 30 of 2004 on Notary Title.